Associations between Chinese/Asian versus Western mass media influences and body image disturbances of young Chinese women. (June 2016) - Jackson, Todd; Jiang, Chengcheng; Chen, Hong
Highlights: Chinese versus Western mass media influences were assessed in young Chinese women. Women reported more pressure, comparisons, and preferences for Chinese than Western media. Pressure from Chinese media was the strongest unique correlate of body image concerns. Chinese rather than Western media scales had more salience for women's body image. Abstract: In this study, we evaluated associations of experiences with mass media imported from Western nations such as the United States versus mass media from China and other Asian countries with eating and body image disturbances of young Chinese women. Participating women ( N = 456) completed self-report measures of disordered eating, specific sources of appearance dissatisfaction (fatness, facial features, stature), and Western versus Chinese/Asian mass media influences. The sample was significantly more likely to report perceived pressure from, comparisons with, and preferences for physical appearance depictions in Chinese/Asian mass media than Western media. Chinese/Asian media influences also combined for more unique variance in prediction models for all disturbances except stature concerns. While experiences with Western media were related to disturbances as well, the overall impact of Chinese/Asian media influences was more prominent.